Geochemical Evaluation of Tang and Pirgal Mud Volcanoes in Order to Estimate Sulfate-Reducing Bacteria Growth - Parsia, Yasaman; Sorooshian, Shahryar (Research India Publications, 2016)
Mud volcanoes are important complications morphological that made of clay. In this study, geochemistry factors of Tang & Pirgal mud volcanoes on growth of Sulfate-Reducing Bacteria (SRB) is investigated based on chemical analysis required factors for growth this group of bacteria (temperature, EC, pH, Na, Ca, Mg, Fe, K and total sulfur) and growth in their specific medium. Temperature, EC, and pH evaluated by their specific devices, sodium and potassium elements evaluated by flame photometer method and calcium, magnesium and iron evaluated with atomic absorption method. The growth of SRB assessed in their specific medium (Postgate's B Medium). The results were as follows that 11 samples showed growth in their medium and results of chemical analysis included that T:24/46°C, pH:8/76, EC:18/29ms/cm, Na:38ppm, K:37ppm, Mg:1/499ppm, Ca:0/264ppm, Fe:0/181ppm and TS:886/91ppm for samples of Tang and T:28/56°C, pH:9/03, EC:15/86ms/cm, Na:32ppm, K:52ppm, Mg:0/707ppm, Ca:0/141ppm, Fe:0/021ppm and TS:724/90ppm for samples of Pirgal. All archived factors are effective for growth of SRB.